Background concentrations and quality reference values for some potentially toxic elements in soils of São Paulo State, Brazil - Nogueira, Thiago Assis Rodrigues [UNESP]; Abreu-Junior, Cassio Hamilton [UNESP]; Alleoni, Luís Reynaldo Ferracciú; He, Zhenli; Soares, Marcio Roberto; Santos Vieira, Camila dos; Lessa, Luís Gustavo Frediani [UNESP]; Capra, Gian Franco (Elsevier, 2018)
Quality reference values (QRV) for potentially toxic elements (PTE) in soils are established as a tool for prevention and monitoring of soil pollution. These values should be periodically revised in order to ensure soil safety for agricultural purposes. Brazil is market leader for several commodities; therefore, the safety of Brazilian soils is of worldwide strategic importance. The objective of this study was to determine the natural background concentrations and the QRV for As, Ba, Cd, Cr, Ni, Pb, Se, and Zn by investigating 30 representative pedotypes in the São Paulo State, one of the most important agro-industry economy at worldwide level. Multivariate statistical analysis was applied to determine the sources of PTE and their variability. The mean natural background concentrations of PTE in the soils were generally lower to those reported in literature. QRV, calculated for each element as the 75th and 90th percentiles, were lower (75th for As, Cd, Pb, and Zn), similar (75th for Ba, Cr, and Se) or above (90th for Ba, Cr, and Se and 75-90th for Ni) those previously proposed by the Brazilian environmental protection agencies. The results indicate that 75th percentile may be too restrictive. The PTE in the investigated soils appear to have comes mainly from two primary natural sources: a prevalent one of geogenic and a secondary of pedogenic origin. These results confirm the predominant natural source of selected PTE in the investigated soils, thus sustaining the possibility of using the data set to develop QRV for the State of São Paulo.
Keywords: Environmental monitoring; Guideline values; Multivariate statistic; Soil contamination; Soil quality